PERBANDINGAN TINGKAT KEBUGARAN JASMANI DAN FAKTOR LINGKUNGAN SOSIAL BUDAYA PADA PEMAIN SEPAKBOLA - M. Habib Albab; Ade Jubaedi; Heru Sulistianta (JUPE (Jurnal Penjaskesrek), 2015)
Purpose of study comparison of the level of physical fitness and socio-cultural environment factors on football players of Catur Tunggal football school Bandar Lampung and football playersof amor junior football school Metro under 12 yearsto determine the differences in the level of physical fitness and environmental factors, social and cultural life of football players of amor junior school Metro with football player of Catur Tunggal school Bandar Lampung. This study method is using qualitative descriptive study for the process of collecting research using triangulation, member checking and expert opinion. The result of this study showed differences in physical fitness respondents football players of Amor Junior school as good category(18,5) and respondents of football players of Catur Tunggal school as less category(15,1). Social and culture environment of the football players Amor Junior school as high physical activity and football players Catur Tunggal school in the urban shows low physical activity.Tujuan penelitian perbandingan tingkat kebugaran jasmani dan faktor lingkungan sosial budaya pada pemain sepakbola sekolah sepakbola catur tunggal kota bandar lampung dan pemain sepakbola sekolah sepakbola amor junior metro di bawah usia 12 tahun untuk mengetahui perbedaan tingkat kebugaran jasmani dan faktor lingkungan sosial budaya pemain Sekolah Sepakbola Amor Junior Metro dengan pemain Sekolah sepakbola Catur Tunggal Bandar Lampung. Metodologi penelitian ini menggunakan metode deskriptif kulitatif untuk proses pengumpulan data menggunakan triangulasi, member checking dan expert opinion. Hasil penelitian ini menunjukan perbedaan kebugaran jasmani responden pemain sekolah sepakbola Amor Junior termasuk kategori bagus (18,5) dan responden pemain sekolah sepakbola Catur Tunggal termasuk kategori kurang (15,1). Lingkungan sosial budaya pemain sekolah sepakbola Amor Junior di pedesaan dengan aktivitas fisik yang tinggi dan pemain sekolah sepakbola Catur Tunggal di perkotaan menunjukan aktivitas fisik yang rendah.Kata kunci: kebugaran jasmani, lingkungan sosial budaya, sepakbola